Performance of Cenchrus purpureus varieties tolerant to salinity under the edaphoclimatic conditions of Granma province, Cuba - Álvarez, Y.; Herrera, R.S.; Ramírez, J.L.; Verdecia, D.M.; Benítez, D.; López, S. (Cuban Journal of Agricultural Science, 2024)
Using a random block design and four replications, the productive performance and quality of salinity - tolerant Cenchrus purpureus varieties (CT-500, CT-502, CT-504, CT-508) was studied and compared with CT-115 under the edaphoclimatic conditions of Granma province at different regrowth ages (45, 60, 75 and 90 days). There were evaluated length and width of leaves and internodes, plant height, leaves and stem percent, leaf area, Absolute Growth Rate and Relative Growth Rate, dry matter yield and the quality indicators CP, NDF, ADF, ADL, DMA and bovine intake index. There was significant interaction (P<0.05) and increases with the regrowth ages, for the length of leaves, internodes, plant height, leaves width and leaf area with 136.75 cm, 20.10 cm, 187.50 cm (CT-504), 4.18 cm and 549.75 cm2 for CT-115 at 90 days, respectively, although there were not differences for this variable in CT-500 and CT-502 varieties. The highest Relative and Absolute Growth Rate during the rainy season were for CT-115 at 60 days with 3.12 cm.day-1 and 0.0173 cm.cm-1.day-1, respectively, and for the components of the cell wall (NDF, ADF and ADL) with values of 70.93 %, 39.20 % and 4.89 % at 90 days for CT-504 (NDF and ADF) and CT-500 (ADL). There were decrease of CP and DMD in 6.64 and 16.59percentage units respectively, with the highest values at 45 regrowth age (11.90 and 67.73 %) in CT-115 and CT-502 varieties. The intake index was increased until 60 days with it highest value (114.95 g.kg-1 LW) for CT-115. The effect of the interaction variety x regrowth age in salinity –tolerant Cenchrus purpureus varieties in the morphological indicators, yield and nutritive quality was showed in this study and the best morphological indicators, yield, growth rate and components of the cell wall in CT-504 and CT-508 were obtained, while CT-115 was higher in leaf area, digestibility and intake index. These varieties can be an option for cattle feeding in soil of medium and low salinity of the eastern region of the country.